Bioremediation of Heavy Metals via Living Microorganisms from Synthetic Wastewater - Topaloglu, Yasar Emre; Nuhoglu, Yasar (Mehmet Sinan Bilgili, 2022)
In this study, the treatment and bioremediation of synthetic wastewater via living microorganisms were investigated. It was thought that the use of rapidly growing microorganism species living in extreme living environments would be effective in treating heavy metals in wastewater. Microorganisms living on the surfaces of stone monuments were preferred as the extreme living environment, and microorganisms isolated from these medium were used. Around 20 bacterial and fungal species living on the stone surface were identified and in this research, which was carried out as a preliminary study, bioremediation studies were carried out with Penicillium frequentans and Penicillium jensenii fungi species, which show very rapid development. Fungi such as Penicillium frequentans, Penicillium jensenii, Trichoderma koningii, Cladosporium cladosporoides and Aspergillus flavus are used some elements for their development by dissolving iron, manganese and potassium in the structure of the stone by enzymatic chemical reactions. In the preliminary experiments, bioremediation of heavy metals such as iron(II) chloride, iron(II) sulfate, aluminum sulfate, copper(II) sulfate compounds were studied. In the preliminary researches, it was determined that the removal of iron(II) sulfate, iron(II) chloride and aluminum sulfate compounds among these compounds was good treatment performance. Iron(II) sulfate and aluminum sulfate compounds, which show good removal in the purification process, were preferred. As a result of the studies, it was determined that the removal efficiency of heavy metals in iron(II) sulfate, aluminum sulfate, compounds was close to 100% (99.30%) for the iron element, but around 94.20% for the aluminum (sulphate).
Keywords: bioremediation; ferrous sulfate; aluminum sulfate; Penicillum spp; Engineering; Environmental Sciences & Ecology